Selection criteria and the skill composition of immigrants: a comparative analysis of Australian and US employment immigration - Guillermina Jasso; Mark Richard Rosenzweig (Institute for the Study of Labor (IZA), 2008)
This paper uses survey data on employment immigrants in Australia and the United States to identify the main determinants of the size and skill composition of employment immigrants to developed countries. Our approach emphasizes the key roles of world prices of skills and country proximity. Our empirical results are consistent with the view that these factors, rather than the nuances of selection systems, dominate. There are five main findings: (1) Higher skill prices in sending countries decrease the number of immigrants but increase their average schooling. (2) More-distant countries send fewer but more skilled immigrants. (3) Given skill prices and proximity, countries with higher income send more immigrants, of lower skill. (4) Within a sending country, Australia attracts less total but higher-skill migrants than does the United States. This can be attributed, however, to the fact that the skill price in Australia is lower than the U.S. skill price, so that immigration gains are greater from immigrating to United States. (5) The estimated coefficients determining migration flows to Australia and the United States are the same for both countries. We conclude that geography thus matters in the sense that who a country's neighbors are, in terms of their level and type of development, has a significant effect on the size and skill composition of employment migrants. There is no evidence that the differences in the selection mechanism used to screen employment migrants in the two countries play a significant role in affecting the characteristics of skill migration.
urn:nbn:de:101:1-2008062766
Keywords: F22; 330; Immigration policy; immigrant selection criteria; skill prices; country proximity; employment immigration; highly skilled immigration; globalization; Internationale Arbeitsmobilität; Qualifikation; Migrationspolitik; Entfernung; Hochqualifizierte Arbeitskräfte; Globalisierung; Vergleich; USA; Australien